PENGARUH KOMITE AUDIT DAN KUALITAS AUDIT TERHADAP NILAI PERUSAHAAN: Studi Kasus Pada Perusahaan Food And Beverage Di BEI Periode 2018-2022 - Khoirunnisa Cahya Firdarini (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
This study aims to examine the influence of the role of the audit committee in a company and audit quality on firm value both partially and simultaneously in food and beverage companies. The number of research samples is 110. The data collection method uses secondary data with financial report data sources and the company annual report. Based on the results of hypothesis testing carried out with multiple regression analysis, the results show that: (1) audit committee has a positive effect on firm value and (2) audit quality has no effect on firm value.